Комплекс споруд ранньомодерного часу Підборецького монастиря на острові Дубовець в околиці Дубна - Пшеничний, Ю.Л.; Бардецький, А.Б. (Археологія і давня історія України, 2021)
Стаття висвітлює результати дослідження
об’єктів забудови та планування Свято-Вознесенського жіночого монастиря на острові Дубовець.
У ній характеризуються конструктивні особливості відкритих споруд та розглядаються виявлені у них археологічні матеріали. В результаті
аналізу розглянутих об’єктів встановлено випадки
перепланування, перебудови та ремонтів будівель
монастиря, які простежено на конкретних прикладах. Опубліковані матеріали дозволяють відтворити окремі сторінки розвитку архітектурно-планувальної організації комплексу монастиря. On the territory of Pidboreckyi monastery, the complex
of unknown buildings opened. They allow reconstructing
some parameters of monastery buildings and
give possibility to image better the planning situation
of the east side of monastery territory during all time of
its existing. Information about that how the part of Ostriv
Dubovets had been adapted for dwelling, economic
and utilized constructions for monastery requires had
got. One of the main results is that the build periods,
facts of repair and replanning of monastery buildings
found out. After 1660s, there were weighty construction
and repair works in the monastery. The great garbage
(object 2) that started used after 1600 conserved
in the middle of XVII c. On this place, the new dwelling
building with the large stove was build. It is possible
and co-ordinate with archaeological materials that this
building could existed until the end of the monastery
history. Then the new economic buildings constructed
near that one. The new garbage replaced on the east
beyond the limits of this new building.
On the excavated area 2 no long-lasting dwelling
or economic constructions were found. It may means
that the monastery yard situated here. Objects 23, 30,
34, and 37 had materials identical to the complex from
the garbage (object 2) in excavated area 1. However,
they are much smaller, which indicate the necessary
in meanwhile garbage pits. Charcoals, everyday tools,
dismantled constructions of stoves were dropped here.
The forming of these objects caused by repaired works
after 1660s. In the second part of XVIII — first part of
XIX centuries the territory of cemetery widen on this
place. The 55 graves excavated here. The facts of reconstruction
and repair of monastery economic buildings
showed on the examples of objects 10 and 12.